Exploring Coastal Green Infrastructure (CGI): A Promising Approach to Mitigating Climate Change-Related Disasters in West Java’s Southern Coast, Indonesia - El Ghifari, Muhammad Raka; Romdani, Andhy; Amanulloh, Fahmi Rahmat; Empung, Empung; Putri, Tryantini Sundi; Mudatsir, Mudatsir (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2025)
Coastal Green Infrastructure (CGI) is increasingly recognized as a nature-based solution to address climate-related challenges such as sea-level rise, coastal erosion, and flooding. However, there remains a lack of standardized and the implementation of CGI resolves the limitation of globally adaptable methods for identifying selecting optimal CGI implementation sites, particularly in tropical coastal regions with diverse environmental characteristics. This study aimed to develop an alternative assessment approach by constructing in assessing CGI potential, focusing on the CGI Coastal Protection Index and CGI Coastal Vulnerability Indices, specifically tailored to tropical coasts. The method incorporated ecological and physical indicators derived Index, with a specific emphasis on tropical coast. Using a comprehensive case study from remote sensing and the southern coast of West Java, the research combines literature review, spatial analysis and was applied to the southern coastal region of West Java, Indonesia, and decision-making frameworks to identify key indicators in developing these indexes. The findings reveal that this region is highly vulnerable to climate-induced coastal hazards, with insufficient existing protection and relatively low CGI implementation potential. By proposing a practical and location-sensitive assessment framework, this study fills a methodological gap in CGI research and offers. This study advances the nature-based coastal protection researches by providing a practical evaluation method of the CGI potential, addressing the existing research gap in tropical environments, and offering valuable insights for advancing coastal management strategies in tropical settings.Keywords: Coastal Green Infrastructure (CGI), climate change, coastal protection, coastal vulnerability, southern coast of West Java.